Administrative legal relations with the participation of the State Bureau of Investigation - А. Т. Komziuk; Ye. А. Lypii (Bulletin of Kharkiv National University of Internal Affairs)
The essence, characteristics, and types of administrative legal relations involving the State Bureau of Investigations have been identified. Additionally, suggestions and recommendations for improving the legal foundations of these relations have been formulated.